2022
DOI: 10.3390/economies10020043
|View full text |Cite
|
Sign up to set email alerts
|

Stock Price Forecasting for Jordan Insurance Companies Amid the COVID-19 Pandemic Utilizing Off-the-Shelf Technical Analysis Methods

Abstract: One of the most difficult problems analysts and decision-makers may face is how to improve the forecasting and predicting of financial time series. However, several efforts were made to develop more accurate and reliable forecasting methods. The main purpose of this study is to use technical analysis methods to forecast Jordanian insurance companies and accordingly examine their performance during the COVID-19 pandemic. Several experiments were conducted on the daily stock prices of ten insurance companies, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 105 publications
0
9
0
Order By: Relevance
“…Similarly, Yogesh et al compared exponential moving average and ARIMA in forecasting prices of 15 stocks in the National Stock Exchange of India, 9 while Shahid et al compared exponential moving average, double exponential moving average, and Holt‐Winters method in forecasting stock prices of two IT companies 10 . Besides, Altarawneh et al compared moving average, weighted moving average, exponential moving average, and exponential decay weighted average in forecasting stock prices of Jordan insurance companies 11 …”
Section: Related Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Yogesh et al compared exponential moving average and ARIMA in forecasting prices of 15 stocks in the National Stock Exchange of India, 9 while Shahid et al compared exponential moving average, double exponential moving average, and Holt‐Winters method in forecasting stock prices of two IT companies 10 . Besides, Altarawneh et al compared moving average, weighted moving average, exponential moving average, and exponential decay weighted average in forecasting stock prices of Jordan insurance companies 11 …”
Section: Related Researchmentioning
confidence: 99%
“…10 Besides, Altarawneh et al compared moving average, weighted moving average, exponential moving average, and exponential decay weighted average in forecasting stock prices of Jordan insurance companies. 11 However, these methods of time series analysis tend to be dragged to previous values; it was pointed out that one-period-ahead forecast follows actual values of the preceding period, while n-periods-ahead forecast follows predicted values of previous periods; thus, there is a limit to improving forecast accuracy. 12 In this context, the present study is aimed at better forecasting of financial time series; particularly, an improved leading indicator is used to mathematically advance a F I G U R E 1 Moving average for monotone increasing function.…”
Section: Related Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Altarawneh et al [ 33 ] found that prediction and analysis of financial data-like insurance premium are a difficult task for any time series data. In their study, they examine the stock prices performance of ten insurance companies of Jordan using higher-order nonparametric Exponential Decay Weighted Average (EDWA).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Another direction in further development of technical analysis is adapting its tools concerning volatile stock markets, including the emerging and crisis ones (Altarawneh, 2022;de Souza et al, 2018;Lubnau & Todorova, 2014;Chong et al, 2010). The paper's authors (de Souza et al, 2018) developed an automated trading system that simulated trades in this portfolio using the methods of technical analysis and fundamental indicators.…”
Section: Introductionmentioning
confidence: 99%